How frequently firms export? Evidence from France - Gábor Békés; Lionel Fontagné; Balázs Muraközy; Vincent Vicard (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
This paper proposes studying export frequency of firms. While extensive margins of products and destination define the scope of firm's export, export shipment frequency is determined by sale method choice and cost structure of the trade technology. Exporters optimize the frequency of international trade transactions to save on costs and gain maximum exposure to clients. Their decisions can be related to a more general problem a la Baumol (1952), where the choice is about the optimal number of transactions in presence of a fixed cost and variable transportation costs. This opens an additional margin of trade: the number of shipments of a firm to a given market in a year. While extensive margins of products and destination define the scope of firm's export, export shipment frequency is determined by sale method choice and cost structure of the trade technology. This paper both presents a framework to think about shipment frequency and analyzes its behavior on French data. We argue that given the decision to export and the anticipated demand, the decision on the number of shipments is guided by the trade technology. In line with the Baumol-Tobin model, the optimal number of shipments will be positively afiected by demand (controlling for distance to destination) and inventory costs and negatively affected by the fixed cost of shipment. Using monthly firm-productdestination level export data from France, we show that key predictions of the model are validated in a gravity model setting that also allows for comparing various margins of trade. During the recent trade collapse, our results point to a strong resilience of export ows despite the drop in demand, which was mainly absorbed at the intensive margin.
Keywords: D40; F12; R40; 330; Gravity; transport costs; frequency of trade; Baumol-Tobin model; customs data; Export; Transportkosten; Regressionsanalyse; Panel; Frankreich